2020
DOI: 10.1038/s41598-020-58010-w
|View full text |Cite
|
Sign up to set email alerts
|

The optimal sequence of bronchial brushing and washing for diagnosing peripheral lung cancer using non-guided flexible bronchoscopy

Abstract: The optimum sequence of bronchial brushing and washing for diagnosing peripheral lung cancer, defined as an invisible endobronchial tumour, is not clear and requires further study. We prospectively obtained washing samples after brushing in patients with peripheral lung tumours during non-guided flexible bronchoscopy (FB) to investigate the diagnostic yield of these samples and conducted a retrospective review of the prospectively collected data. The study included 166 patients who met the inclusion criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Even if the target lesions are quite small, bronchial brushing enables sufficient tumor cells collection. 12 Third, even when fresh frozen samples are required, pathological confirmation is still possible by dividing the same sample into two tubes (Figure 1). A few studies have reported on the feasibility of TBB for NGS analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even if the target lesions are quite small, bronchial brushing enables sufficient tumor cells collection. 12 Third, even when fresh frozen samples are required, pathological confirmation is still possible by dividing the same sample into two tubes (Figure 1). A few studies have reported on the feasibility of TBB for NGS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, it is difficult to obtain sufficient tumor cells from small lung nodules by forceps biopsy. Even if the target lesions are quite small, bronchial brushing enables sufficient tumor cells collection 12 . Third, even when fresh frozen samples are required, pathological confirmation is still possible by dividing the same sample into two tubes (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Jo KW's study, they excluded patients with endobronchial diseases. Recently, Lim and his colleagues showed that bronchial brushing and washing could increase the diagnostic yield for patients with invisible endobronchial tumors (13). Possibly, this procedure may be beneficial for solid tumors.…”
Section: Discussionmentioning
confidence: 99%